2022
DOI: 10.3390/nu14153210
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Prevalence of Eating Disorders among Dietetics Students and Students of Other Fields of Study at Selected Universities (Silesia, Poland)

Abstract: Background: Over the past few years, an increase in the incidence of eating disorders has been noted. An increase in the pace of life, an increase in the availability of a wide variety of food products, and, to a large extent, the involvement of mass media are cited as reasons for this phenomenon. The promotion of a slim figure by the mass media is equated with achieving success in life, but also the advertising of a wide selection of food products (often highly processed) can have a serious impact on the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…The majority of our participants (71.0%) were of normal weight according to the WHO BMI classification, in line with other studies reporting similar rates for dietetics students [14,56] but in contrast with the lower rate (54.0%) reported by Rusil and Harith. Another study suggested that dietetics students are no more or less prone to negative attitudes towards obesity than their peers [57,58].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The majority of our participants (71.0%) were of normal weight according to the WHO BMI classification, in line with other studies reporting similar rates for dietetics students [14,56] but in contrast with the lower rate (54.0%) reported by Rusil and Harith. Another study suggested that dietetics students are no more or less prone to negative attitudes towards obesity than their peers [57,58].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies reported a high prevalence of ON ranging from 41.9% to 88.7% [ 8 , 16 , 17 , 20 , 51 , 55 ], and a prevalence of ED ranging from 12.9% to 15.4% among dietetics students and dieticians [ 12 , 17 ]. An international study with data from 14 countries found that 77.0% of dieticians believe that EDs are a problem for dietetics students [ 11 ], and a study in South Africa observed a higher risk of EDs in dietetics students than in students in other fields [ 14 , 56 ]. Kassier and Veldman showed a higher risk of ED among first-year nutrition and dietetics students (33.3%) in South Africa compared with students in non-nutrition-related courses (16.9%) [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to another study by one of the authors of the present study, Grajek, it appears that the risk of orthorexia is higher in people who are characterized by a rational diet and higher physical activity. In addition, according to data from the EAT-26 questionnaire, the authors of the studies estimated that there is a higher risk of eating disorders among people with specialized knowledge (dietetics students) [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, nutrition students are “fed” during classes with constant messages about proper nutrition. All of these factors can give rise to an obsession with food, proper eating habits, and outward appearance [ 34 ]. The importance of research on food habits and potential eating disorders in this population lies in the knowledge of both appropriate and inappropriate strategies and patterns.…”
Section: Discussionmentioning
confidence: 99%